Leiomyosarcoma of Urinary Bladder, A Review of Two Cases. (28th October 2020) - Fakhri, N; Bhalla, R
Abstract: Introduction/Objective: Leiomyosarcomas of the urinary bladder are rare smooth muscle tumor, and constitute 1% of all bladder malignancies. Although rare, leiomyosarcoma is a clinically significant disease, presenting as a high-grade advanced malignancy with associated substantial morbidity and mortality, if not treated early. The diagnosis can be delayed because of the asymptomatic presentation until the tumor reaches an advanced stage. Methods: We present two cases of leiomyosarcoma of the urinary bladder. First case: a 63 years old female with a history of cervical carcinoma treated with radiation, 25 years ago, followed by uncomplicated clinical course, until recent development of vesicovaginal fistula. During her work up with cystoscopy, a large bladder mass was identified. Second case: a 71 years old female with a history of treated breast cancer, who presented with recurrent history of cystitis and hematuria. Cystoscopy revealed a nodular mass in the right posterior bladder wall. Results: Microscopically, both lesions were highly cellular with infiltrative, interlacing fascicles of spindle cells and associated mitosis, cellular atypia and necrosis. Immunohistochemistry revealed positive expression of muscle- specific actin, desmin, and caldesmon; with negative expression of ALK-1, EMA, Cytokeratins and GATA3, in both the cases. Other spindle cell lesions including, leiomyoma, inflammatory myofibroblastic tumor and sarcomatoid carcinoma were included in the differential diagnosis, and ruled out by morphology and immunohistochemistry. Conclusion: Our cases highlight the importance of awareness of the occurrence of leiomyosarcomas, a rare manifestation in bladder. Although rare, but they present with a poor outcome. The differential diagnosis of spindle cell lesions is extensive, including close benign and malignant mimics, the treatment of all being very different. Immediate radical cystectomy has been associated with longer survival rates for leiomyosarcoma. Leiomyosarcoma, being aggressive, with associated high recurrence rate and metastatic potential, an early correct diagnosis would aid in the institution of proper management.